ASSESSMENT OF THE DEVELOPMENT OF THE FUNCTIONING OF REMOTE BANKING SERVICE IN UKRAINE - CHEREP, OLEKSNDR; KHMELKOVSKA, TETYANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Digital technologies have long affected every field of activity, including the banking sector. They greatly facilitate the work of organizations and are the key to their long-term development. Given that digitalization has long been a trend in the banking sector, it was last year that all the "players" were able to truly appreciate the real benefits of the new customer service format. Ukrainian digital banking could have developed in the shadow of classic banking for a long time, but the global pandemic COVID-19 changed all plans and became a kind of driver for the accelerated digital transformation of the banking business. Successful economic development of the state is impossible without a well-developed banking system, the state of which is influenced by both the domestic economic and political situation and changes in the world banking system. These changes are the result of deep macroeconomic processes in the world economy (integration, liberalization, sharp scientific and technological rise) and they affect all banks, regardless of their level of development. One of the main features of the modern domestic banking system is the rapid development of computer and telecommunications technologies, the introduction of network devices, which reduces information processing time, allows comprehensive automation, develop mechanisms for remote customer service and offer a new range of services. In addition, the rationalization of the payment system in the country requires a significant reduction in cash transactions in favor of non-cash payments. The widespread introduction of remote banking technologies has become a major innovation for banks around the world. The introduction of Internet banking and mobile banking is due to the development of the banking system under the influence of technological progress and a high level of competition in the field of banking services. Most experts believe that the Internet is one of the most effective tools for promoting banking products, due to the significant spread of Internet use in general and the active promotion of banks in the Internet.